2019
DOI: 10.1088/2053-1583/ab3167
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial stress transfer in strain engineered wrinkled and folded graphene

Abstract: Because of its large surface area and flexibility, graphene has been explored for various applications such as flexible electronics and energy storage. Topographical undulations are commonly generated in graphene artificially by pre-strain and annealing to allow more tunable properties in hierarchical patterns. It is also possible, however, that strain engineering may induce negative effects, such as inhomogeneous strain distribution and fracturing of graphene. However, the correlation between those negative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…These morphologies of 2D materials can result in unexpected complexity in mechanical performance 26 and interfacial stress transfer. 32 , 34 Therefore, in this study, such MXene flakes were avoided for the micromechanical characterization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These morphologies of 2D materials can result in unexpected complexity in mechanical performance 26 and interfacial stress transfer. 32 , 34 Therefore, in this study, such MXene flakes were avoided for the micromechanical characterization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…At the folds, the strain in graphene was mostly relaxed by the out-of-plane deformation ( 34 ). Since the out-of-plane folds effectively resulted in lower global in-plane stiffness and the stress transfer efficiency is also lower at the buckles ( 35 ), the motion/deformation of each small region was more independent and noncoherent due to geometrical asymmetry and edge effect. Previous study on Raman mapping of graphene revealed highly nonuniform strain distributions when applying substrate strain of higher than even 0.6% ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted at this point that the definition of wrinkling is very broad thus its effect is difficult to quantify. Finally, in a very recent study, Li et al 235 came up with an analytical equation to quantity the effect of different types of wrinkles and folds on graphene, after applying strain engineering to wrinkled and folded graphene. It was found that wrinkles do not reduce the reinforcement efficiency significantly when majority of graphene still conforms to substrate, while when graphene detaches from substrate its efficiency drops significantly as a result of delamination.…”
Section: Nanoscale Reviewmentioning
confidence: 99%